Determining factors in shaping the sustainable behavior of the generation Z consumer - Dragolea, Larisa-Loredana; Butnaru, Gina Ionela; Kot, Sebastian; Zamfir, Cristina Gabriela; Nuţă, Alina-Cristina; Nuţă, Florian-Marcel; Cristea, Dragoş Sebastian; Ştefănică, Mirela (Frontiers in Environmental Science, 2023)
Introduction: Organizations currently emphasize green marketing strategies by implementing marketing practices, aiming to design, produce, promote and sell green products. Thus, both consumers and producers have turned their attention to the category of environmental friendly products, taking into account that the concept of green marketing is now being given greater importance. Responsible organizations have begun to adapt their strategies in production, promotion and interaction activities with consumers or potential consumers of organic products in the context we are going through, when environmental protection becomes an imperative. Analysis of the sustainable behavior of Generation Z is a determining factor from the perspective of the task that this generation will naturally take on, in terms of environmental responsibility. Methods: The research aims to determine the profile of the Generation Z consumer, in order to adapt the strategic actions of the government or organizations to direct and educate as objectively and efficiently as possible towards adopting the principles of ecological, sustainable and responsible consumption. Based on the data collected through a survey, we analyzed the sustainable behavior of Generation Z consumers studying at Romanian universities where there are specializations in this field. The research is quantitative, using structural equation modelling with partial least squares (PLSSEM) to test the hypotheses regarding the relationship between the determining factors and the sustainable behavior of Generation Z consumers. Results and Discussion: The results show that there is a positive relationship between both the sustainable behavior of Generation Z consumers and the satisfaction it conveys to them, as well as their environmental protection activities. However, there is no relationship between the sustainable behavior of Generation Z consumers and the green marketing practices of the organizations, environmental issues and their identification with the environmentally responsible consumer.